Octopus djinda (Cephalopoda: Octopodidae): a new member of the Octopus vulgaris group from southwest Australia - Amor, Michael D.; Hart, Anthony M. (Zootaxa, 2021)
A new Octopus Cuvier, 1797 species, Octopus djinda Amor, 2021 (previously treated as O. cf. tetricus and O. aff. tetricus), is described from the shallow waters off southwest Australia. This species was classified as conspecific with O. tetricus Gould, 1852 from Australia’s east coast and New Zealand but is shown here to be morphologically and genetically distinct. This description is based on 25 individuals across three localities in southwest Australia, encompassing most of its distribution. Greater and non-overlapping sucker counts on the males hectocotylised arm delimit east and west coast forms. DNA barcoding using cytochrome c oxidase subunit I also successfully differentiates between these taxa; 13 polymorphisms along a 349 bp partial fragment (3.7% sequence divergence). A close relative of the O. vulgaris Cuvier, 1797 species-group, O. djinda, sp. nov. supports a highly productive fishery and is currently one of two octopod fisheries worldwide to have received sustainable certification from the Marine Stewardship Council. The taxonomic description presented here provides formal recognition of the taxonomic status of southwest Australia’s common octopus, O. djinda, sp. nov. and facilitates appropriate fisheries catch reporting and management.